Cryogenic brines as diagenetic fluids: Reconstructing the diagenetic history of the Victoria Land Basin using clumped isotopes. (1st March 2018) - Staudigel, Philip T.; Murray, Sean; Dunham, Daniel P.; Frank, Tracy D.; Fielding, Christopher R.; Swart, Peter K.
Abstract: The isotopic analyses (δ 13 C, δ 18 O, and Δ47 ) of carbonate phases recovered from a core in McMurdo Sound by ANtarctic geologic DRILLing (ANDRILL-2A) indicate that the majority of secondary carbonate mineral formation occurred at cooler temperatures than the modern burial temperature, and in the presence of fluids with δ 18 Owater values ranging between −11 and −6‰ VSMOW. These fluids are interpreted as being derived from a cryogenic brine formed during the freezing of seawater. The Δ47 values were converted to temperature using an in-house calibration presented in this paper. Measurements of the Δ47 values in the cements indicate increasingly warmer crystallization temperatures with depth and, while roughly parallel to the observed geothermal gradient, consistently translate to temperatures that are cooler than the current burial temperature. The difference in temperature suggests that cements formed when they were ∼260 ± 100 m shallower than at the present day. This depth range corresponds to a period of minimal sediment accumulation from 3 to 11 Myr; it is therefore interpreted that the majority of cements formed during this time. This behavior is also predicted by time-integrated modeling of cementation at this site. If this cementation had occurred in the presence of these fluids, then the cryogenic brines have been a longstanding feature in the Victoria Land Basin. Brines such as those found at this site have been described in numerous modern high-latitude settings, and analogous fluids could have played a role in the diagenetic history of other ice-proximal sediments and basins during glacial intervals throughout geologic history. The agreement between the calculated δ 18 Owater value and the measured values in the pore fluids shows how the Δ47 proxy can be used to identify the origin of negative δ 18 O values in carbonate rocks and that extremely negative values do not necessarily need to be a result of the influence of meteoric fluids or reaction at high temperature.